Time discretization versus state quantization in the simulation of a one-dimensional advection–diffusion–reaction equation. (January 2016) - Bergero, Federico; Fernández, Joaquín; Kofman, Ernesto; Portapila, Margarita
In this article, we study the effects of replacing the time discretization by the quantization of the state variables on a one-dimensional (1D) advection–diffusion–reaction (ADR) problem. For that purpose the 1D ADR equation is first discretized in space using a regular grid, to obtain a set of time-dependent ordinary differential equations (ODEs). Then we compare the simulation performance using classic discrete time algorithms and using quantized state systems (QSS) methods. The performance analysis is done for different sets of diffusion and reaction parameters and also changing the space discretization refinement. This analysis shows that, in advection–reaction-dominated situations, the second-order linearly implicit QSS method outperforms all of the conventional algorithms (DOPRI, Radau and DASSL) by more than one order of magnitude.